Biological Nitrogen Fixation: Perspective and Limitation - N D Purwantari (Indonesian Center for Animal Research and Development, 2008)
The demand of chemical fertilizer, N in particular will be increasing until 2020. In Indonesia, the demand of fertilizer from 1999 – 2002 increased 37.5 and 12.4% for urea and ammonium sulphate, respectively. At the same time, the price of this fertilizer is also increasing and it can not be afforded by the farmer. Other problem in using chemical fertilizer is damaging to the soil and environment. One of the problem solvings for this condition is to maximize biological nitrogen fixation (BNF). BNF is the fixation of N atmosphere by association between soil bacteria rhizobia and leguminous plant. BNF is sustainable and environmentally friendly in providing nitrogen fertilizer. Therefore, it would reduce the requirement of chemical nitrogen fertilizer for the plant. Gliricidia sepium fixes 170 kg N/ha/12 months, equivalent with 377 kg urea, Sesbania sesban 179 kg N/ha/10 months, equivalent 397 kg with urea, soybean 26 – 57 kg/2 months equivalent with 57 – 126 kg urea. The amount of N2- fixed varies, affected by species, environmental and biological factors. There are some limitations in applying this technology. The effect of N contribution is very slow at the beginning but in the long term, it would be beneficial for plant production and at the same time, maintain condition of physical and chemical of soil, soil microbes and therefore soil fertility. Key words: Legume, rhizobia, fixation, N2 atmosphere, fertilizer